Use of the Concrete–Representational–Abstract Instructional Sequence to Improve Mathematical Outcomes for Elementary Students With EBD. (April 2022) - Flores, Margaret M.; Hinton, Vanessa M.
The concrete–representational–abstract (CRA) sequence of instruction is an explicit methodology for teaching mathematics using multiple representations of concepts. Learning concepts through multiple representations fosters conceptual understanding and mathematical thinking. This article describes how a special education teacher used explicit CRA instruction with two elementary students with emotional and behavioral disorders. Its aims are to describe and provide a rationale for explicit CRA instruction. We describe lesson activities, methods, materials, and procedures. Finally, we offer suggestions for effective implementation.